2015
DOI: 10.1016/j.molcel.2015.07.031
|View full text |Cite|
|
Sign up to set email alerts
|

Timeless Interacts with PARP-1 to Promote Homologous Recombination Repair

Abstract: Human Timeless helps stabilize replication forks during normal DNA replication and plays a critical role in activation of the S phase checkpoint and proper establishment of sister chromatid cohesion. However, it remains elusive whether Timeless is involved in the repair of damaged DNA. Here, we identify that Timeless physically interacts with PARP-1 independent of poly(ADP-ribosyl)ation. We present high-resolution crystal structures of Timeless PAB (PARP-1-binding domain) in free form and in complex with PARP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 50 publications
(64 reference statements)
3
52
0
Order By: Relevance
“…Although functionally not fully understood, there is much evidence suggesting that dynamic recruitment of PARP-1 to sites of DSB facilitates repair through the HR pathway ( 12 , 43 45 ). Evidence indicates that following its initial recruitment to DSB, PARP-1 is retained at the break site, allowing the local accumulation of PAR polymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although functionally not fully understood, there is much evidence suggesting that dynamic recruitment of PARP-1 to sites of DSB facilitates repair through the HR pathway ( 12 , 43 45 ). Evidence indicates that following its initial recruitment to DSB, PARP-1 is retained at the break site, allowing the local accumulation of PAR polymers.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications are catalyzed by PAR polymerases (PARPs), including the founding member of this family, PARP-1, which promotes the attachment of PAR polymers onto target proteins, a process commonly known as PARylation. PARP-1 activity has been traditionally associated with base excision repair, but clear evidence demonstrates that PARP-1 is recruited to DSB and that PARylation plays an important role in DSB repair, primarily by HR ( 10 12 ). Protein PARylation at break sites may play multiple roles in orchestrating the repair of DSB.…”
Section: Introductionmentioning
confidence: 99%
“…We identified specific gene sets involved in the combination synergism. These genes belong to cell cycle control such as normally activated G2/M cell cycle checkpoints and DNA-damage response and repair pathways (i.e., Timeless, AURKA, MCM2, RAD54L, POLD1, MRE11A) [6164]. Moreover, specific genomic aberrations of these genes differentially characterized HS-C and LS-C. We showed that enzymes involved in DNA-damage response and repair were actually expressed more in cell lines displaying higher PARP1 basal expression and high trabectedin + olaparib synergism.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the TIM Δ1-603 (ΔN) mutant, which fails to bind to TIPIN, still interacts with SDE2, indicating that the interactions of TIM with TIPIN and with SDE2 are mediated by distinct regions of TIM ( Figures S2D and S2E). Previous structural studies demonstrated that TIM directly interacts with PARP1 via TIM's C-terminal PAB (PARP1-binding) domain, located within the D4 region, and identified several residues including E1049, E1056, and T1078 to be essential for PARP1 interaction 40,41 . However, the TIM C-terminal point mutant that fails to bind to PARP1 still retained its interaction with SDE2, suggesting that SDE2 binds to TIM via a region distinct from the PAB domain ( Figure 2H).…”
Section: Sde2 Directly Interacts With the C-terminus Of Timmentioning
confidence: 99%
“…Therefore, TIM in conjunction with CLSPN, may contribute to such processes by regulating the localization and activity of key players that process stalled forks [49][50][51][52] . Intriguingly, TIM is known to interact with PARP1, which has multiple roles in the processing of reversed forks through regulation of proteins such as XRCC1, RECQ1, and MRE11 40,41,53 . The PARP1-TIM complex may be required for the protection of reversed forks by modulating these protein activities, and SDE2 may contribute in the regulation of this process.…”
Section: Roles Of Tim Associated With Fork Protection During Fork Revmentioning
confidence: 99%